Enhancing Self-Esteem, Satisfaction, and Motor Skills through Gamification in Elementary Physical Education - Wibowo, Cahyo (Physical Education Theory and Methodology, 2024)
Objectives. This study aimed to investigate the impact of gamification in physical education on enhancing the self-esteem, satisfaction, and motor skills of 7-9-year-old elementary school students. Materials and methods. This study employed a pre-experimental method using a one-group pretest-posttest design without a control group. The participants were 90 elementary school students aged 7-9 years in Salatiga City (Indonesia), selected through purposive sampling. The research instruments included self-esteem, sports satisfaction, and motor skills assessment tools that have been validated and tested for reliability. The gamified intervention was implemented in physical education instruction over eight weeks. The statistical analysis was conducted using descriptive statistics, prerequisite tests, analysis of variance (ANOVA), and paired samples t-tests. Results. The study’s findings indicate significant changes in the observed variables following the intervention, with a significance value (Sig) of 0.000 < 0.05. The calculated t-values for all three variables were more significant than the critical t-value of 1.990, with a significance level (Sig. 2-tailed) < 0.05. Therefore, this implies that gamification in elementary physical education instruction has a statistically significant positive impact on students’ self-esteem, satisfaction, and motor skills. Conclusions. The findings elucidate that the implementation of a gamification intervention has proven effective in enhancing students’ self-esteem, satisfaction with learning, and motor skills abilities. The practical implications of these findings underscore the importance of considering the integration of gamified process into instructional design as a strategy to enhance the quality of physical education learning in elementary schools.